The Quality Of Tolerance Education Among The Students Of Universitas Pendidikan Nasional - Wiguna, I Made Arsa; Triguna, Ida Bagus Gde Yudha; Wimba, I Gusti Ayu (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2019)
Tolerance has become very important amid the decline in the spirit of nationalism among students lately. Previous studies show that the influence of radical understanding that leads to acts of terrorism has entered the campus area, even the alumni from one of the tertiary institutions in Indonesia are involved in terrorism cases. But not all of the students in tertiary institutions have this attitude. Students at the Universitas Pendidikan Nasional, as the best private tertiary institution in Kopertis Region 8, are able to establish tolerance well. This paper aims to identify and analyze the quality of tolerance education among the students of Universitas Pendidikan Nasional. Therefore, phenomenological approach with data collection techniques through observation, interviews, and documentation are applied to accomplish the purpose of this study. The quality of tolerance education in this study is seen from five dimensions. First, the quality of students? understanding of tolerance education based on their religion. Second, the quality of empathy among students. Third, the quality of tolerance education among students in the learning process. Fourth, the quality of tolerance education among students in organizational activities. Fifth, the quality of tolerance education among students in religious and cultural activities. Based on the observations and interviews, the quality of tolerance education among the students of Universitas Pendidikan Nasional can be stated as good.